Uncovering Competitive and Restorative Effects of Macro- and Micronutrients on Sodium Benzoate Biodegradation - Zaveri, Purvi; Iyer, Aishwarya Raghu; Patel, Rushika; Munshi, Nasreen Shakil (Frontiers in Microbiology, 2021)
A model aromatic compound, sodium benzoate, is generally used for simulating aromatic pollutants present in textile effluents. Bioremediation of sodium benzoate was studied using the most abundant bacteria, Pseudomonas citronellolis, isolated from the effluent treatment plants of South Gujarat, India. Multiple nutrients constituting the effluent in actual conditions are proposed to have interactive effects on biodegradation which needs to be analysed strategically for successful field application of developed bioremediation process. Two explicitly different sets of fractional factorial designs were used to investigate the interactive influence of alternative carbon, nitrogen sources and inorganic micronutrients on sodium benzoate degradation. The process was negatively influenced by the co-existence of other carbon sources and higher concentration of KH2PO4 whereas NH4Cl and MgSO4 exhibited positive effects. Optimized concentrations of NH4Cl, MgSO4 and KH2PO4 were found to be 0.35, 1.056 and 0.3 mg l-1 respectively by Central Composite Designing. The negative effect of high amount of KH2PO4 could be ameliorated by increasing the amount of NH4Cl in the biodegradation milieu indicating possibility of restoration of degradation capability for sodium benzoate degradation in presence of higher phosphate concentration.